Desensitization Protocols for Hypersensitivity Induced by Cytotoxic Drugs; Platinum Salts and Taxanes - Zahid, Maha; Hamid, Husnain; Tahir, Numra; Amjad, Aqsa; Bashir, Irfan; Jamshaid, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
With the expanding use of Platins and Taxanes for cancer patients, a highly concerning threat is observed in the form of Hypersensitivity reactions. To reduce hypersensitivity reactions, different desensitization protocols are formed. The prevalence of hypersensitivity to carboplatin ranges from 1-27%, oxaliplatin 1-19%, cisplatin 5-20%, and docetaxel 10-20%. Even though the hypersensitivity reactions following the administration of oxaliplatin may be less severe than carboplatin hypersensitivity reactions but extremely life-threatening reactions have been observed also. Some patients, allergic to oxaliplatin show uncharacteristic hypersensitivity signs such as chills, fever, and abdominal and/or extreme chest pain. Symptoms followed by Taxanes induced hypersensitivity reactions are flushing, pruritus, and skin rashes to more life-threatening features like dyspnea, hypotension, angioedema, and occurrence generalized pale red bumps on the skin which is also called as urticarial. Numerous preventive methods have been develop to avoid hypersensitivity reactions and the most effective technique so far is the rapid drug desensitization. It allows re-exposure to the culprit drug safely and effectively. Drug desensitization is a whole set of techniques or process by which an offender drug is introduced in the system of a patient following a cycle of very calculated dose augmentation, in a way that the total administered dose is equal to the actual target dose of the drug. Introduced protocols result in better outcomes as expected and now used widely throughout hospitals accordingly.